Producing organic fish through recirculating aquaponics system - Saleem Mustafa (Universiti Malaysia Sabah, 2011)
Aquaponics is the combined culture of aquatic organisms and plants in one integrated unit. Wastewater from fish culture tank is passed to the plant holding tank. Nutrients in the wastewater are taken up by plants to support their growth and the water is recycled. No antibiotics or other harmful chemicals are used to prevent or treat infections, therefore, both crops are produced in an organic way, free from harmful chemicals. In this study, an experiment was designed to determine the compatibility of a popular herb mint, Mentha sp. and a fruiting vegetable tomato, Lycopersicon sp. in one integrated system with tilapia, Oreochromis sp. This was done to understand the effects of this combination towards growth and survival of fish as well as plants. These two plants required different nutrient levels; therefore the nutrient stripping efficiency of plants through assimilation of nutrients in the water was determined. To have a better understanding of the findings, the results obtained were compared with treatments that comprised tilapia integrated with mint or tomato only. The highest growth and survival (85.36±2.07%) of fish was observed in the combined treatments. As for the plants, the highest survival was recorded in the tomato-only treatment (1000/0 survival rate) and in the mint-only treatment (75.0% survival rate). However, there is no Significant difference (P>O.OS) in all of the treatments. The ammonia and nitrate levels in the plant combination treatments also remained low and stable compared to the other treatments. This suggested that the uptakes of nutrients are balanced by mint and tomato, offering the possibility of a stable and sustainable fish culture that can maximize plants production.